2019
DOI: 10.1109/access.2019.2933242
|View full text |Cite
|
Sign up to set email alerts
|

Location-Invariant Physical Layer Identification Approach for WiFi Devices

Abstract: Recently, Radio Frequency Fingerprinting (RFF) becomes a promising technique which augments existing multifactor authentication schemes at the device level to counter forgery and related threats. As RFF leverages the discriminable hardware imperfections reflected in Radio Frequency (RF) signals for device identification, it has a good property of scalability, accuracy, energy-efficiency and tamper resistance. However, its identification accuracy might be compromised when the locations of training and testing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Radiometric fingerprinting can enhance the security of networks by enabling means of additional authentication based on physical layer properties of devices [5,21,23]. However, we found that an adversary can easily impersonate other devices exploiting the fingerprinting scheme proposed by Liu et al [23].…”
Section: Attack Scenario Ii: Compromising Security Via Impersonation Attacksmentioning
confidence: 84%
See 1 more Smart Citation
“…Radiometric fingerprinting can enhance the security of networks by enabling means of additional authentication based on physical layer properties of devices [5,21,23]. However, we found that an adversary can easily impersonate other devices exploiting the fingerprinting scheme proposed by Liu et al [23].…”
Section: Attack Scenario Ii: Compromising Security Via Impersonation Attacksmentioning
confidence: 84%
“…We have also witnessed a variety of masquerading attacks in which the adversary mounts a machine-in-themiddle (MitM) attack by creating a rogue access point (AP), mimicking the identity (i.e., SSID) of a legitimate AP. It has been shown that physical layer security, in particular, radiometric (radio frequency) fingerprinting can thwart such attacks [5,21,23].…”
Section: Introductionmentioning
confidence: 99%
“…RFF identification has been prototyped in conjunction with a number of wireless techniques, such as WiFi [285], [290], ZigBee [287], [291], Bluetooth [292] and LoRa [293]- [295], just to name a few. Because RFF identification exploits the features of wireless transceivers, it is a perfect candidate for key generation in an integrated security framework [87].…”
Section: B Rff Identificationmentioning
confidence: 99%
“…It should be noted that a great majority of CSI enabled researches depend on limited categories of Network Interface Cards (NICs) for data collection, owing to the limitation of CSI Tools [90]. However, the authors in [102] forward way is to remap signals into the time-frequency domain [103]. In [104], the authors use the STFT (Short-Time Fourier Transform) with the SVM algorithm to identify four different transceivers.…”
Section: B Feature-based Statistical Learning For Specific Device Ide...mentioning
confidence: 99%